Galectin-3 impacts Cryptococcus neoformans infection through direct antifungal effects - Fausto Almeida (Nature Portfolio, 2017)
The protein Galectin-3 modulates host immunity and plays roles during infections. Here, Almeida et al. show that this protein contributes to host defence against infection with the fungal pathogen Cryptococcus neoformans by inhibiting fungal growth and inducing lysis of fungal extracellular vesicles.